Ovicidal Activity of Essential Oils against Red Flour Beetle, Tribolium castaneum (Coleoptera: Tenebrionidae) - Mondal, Mina; Khalequzzaman, M (Journal of Bio-Science, 2011)
Context: The essential oils are being tried as potential candidates for pest and disease management. Several essential oils of botanical origin have been reported for their repellant, toxic and developmental inhibitory activities. The ovicidal effect of essential oil is probably the major factor in the suppression of the development of adults from treated eggs. Objectives: To investigate the ovicidal effect of vapours of five essential oils viz., cardamom (Elletaria cardamomum L.), cinnamon (Cinnamomum zeylanicum Blume), clove (Sygium aromaticum L. Merrill. et. Perry), Eucalyptus spp. and neem (Azadirectica indica A. juss) against the eggs of red flour beetle, Tribolium castaneum (Herbst). Materials and Methods: Ten eggs (24 h old) of T. castaneum were placed in each petridish with wheat flour as food medium and without flour medium and then the petridish were kept inside 650 ml jars with screwed lids. Aliquots of 0.5 ml of each dose of essential oils were applied on filter paper attached to the lower side of the lids. The exposure periods were 24, 48, 72 and 96 h, respectively. After treatment periods, petridishes were taken out of the jars and the final mortality counts were made after 11 days. Mortality data were subjected to probit analysis. Results: The oils had high-fumigant activity against eggs and toxicity progressively increased with increase in exposure time and concentration. At the highest concentration of 5.769 mg/l air and exposure period of 24 h, cinnamon oil achieved 100% mortality in flour and without flour media. The vapours of essential oils from cardamom and clove resulted in 100% mortality of the eggs. Neem oil achieved mortalities as high as 51.66 and 50% mortality at the highest concentration and exposure period in with-flour and without flour medium respectively. At a concentration of 5.769 mg/ l air cardamom oil, the LT90 values were 50.80 and 62.78 h for with-flour and without flour medium respectively. Conclusion: The essential oils of cinnamon and clove, proved to be promising as control agents against stored-product insects, especially T. castaneum. Key words: Essential oil; Fumigant toxicity; Ovicidal activity; Tribolium castaneum DOI: 10.3329/jbs.v17i0.7102 J. bio-sci. 17: 57-62, 2009